ANALISIS PENGARUH LINGKUNGAN TOKO, VARIASI PRODUK, PROMOSI PENJUALAN, DAN LAYANAN TENAGA PENJUALAN TERHADAP KEPUASAN KONSUMEN (STUDI PADA ALFAMART H825 SEMARANG, JAWA TENGAH ) - Saputri, Fanny Setiyo; Rahardjo, Susilo Toto (Faculty of Economics and Business Diponegoro University, 2020)
Alfamart H825, located in Semarang, Central Java encounters sale decreasing 28% in 2019 compared to 2018 sale. Based on interviews, the decline in sales turnover was due to the emergence of a new competitor, Indomaret, which the location is close to Alfamart. Besides, based on customer surveys, they were not satisfied enough with the quality of service provided by Alfamart such as the store environment, product availability, services, and limited promotions. Customer satisfaction is important to study because it covers consumer ratings of quality provided by the company in serving the needs of consumers and it roles as dependent variable that is influenced by the independent variables above. This research is aimed to explain the effect of store environment, assortment, services laborers, and sales promotion towards customer satisfaction at Alfamart Jl. Tirto Agung, Banyumanik, Semarang. This research was conducted using survey method and questionnaire that was measured using Likert scale towards the customers of the store. Firstly, questionnaire was distributed to respondents by researcher. Secondly, data are processed by SPSS application version 20. Thirdly, data are analyzed by results of existing research and theories. Fourthly, draw conclusions based on the results of data analysis. There were 105 respondents who were at least, shopping twice per month in this store. The result shows that assortment has positive and significant effect towards customers satisfaction and services laborer has positive and significant effect towards customers satisfactiom while store environment and sales promotion have not positive effect towards customers satisfaction. To increase consumer satisfaction, retail should provide a variety of product (assortment product) so that consumers freedom to choose products according their wants and needs. In addition, retails should improve the ability of salespeople to improve their ability to serve consumers. To increase consumer satisfaction, retailer should provide many assortment product so consumers can choose products that suit their wants and needs. In addition, retail should increases the seller's ability to increase quality of service for consumers.